A mechanistic model for uridine 5′-monophosphate nucleotide synthesis. (29th September 2015) - Rao, N.N. Subrahmanyeswara; Deshpande, Parag A.
Abstract: Uridine 5′-monophosphate synthesis by orotidine 5′-phosphate decarboxylase was modeled taking into account a detailed reaction pathway and formation of all possible intermediates. Contributions from zwitterion mechanism, covalent mechanism, carbene mechanism and kinetic mechanism were taken into account to develop a branched mechanism. The model equations comprising of simultaneous partial differential equations describing the temporal variation of substrate concentrations were simultaneously solved and regression was carried out to determine the optimal rate parameters. The model was successful in describing the kinetics of the reaction with enzyme derived from yeast and predicting the complete substrate consumption for enzyme derived from human domain. The model also correctly described and predicted the substrate inhibition characteristics for both the observations. The model is, therefore, expected to provide reliable kinetic description of the reaction irrespective of the enzyme source. Abstract : Graphical abstract: Abstract : Highlights: A novel mechanistic model for the action of orotidine 5-phosphate decarboxylase proposed. The model proposed is enzyme source-independent. Activity of enzyme derived from yeast and human domain successfully described. Model described yeast-derived enzyme activity to be free from substrate inhibition. Model predicted human-derived enzyme activity to be substrate inhibited.